Mnemonic dan Muscle Memory dalam Inovasi pembelajaran Marfologi Bahasa Arab (Sharaf) sebagai INSTING - Hanifansyah, Nur (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2025)
This study aims to explore the effectiveness of mnemonic and muscle memory strategies in Arabic morphology (Sharaf) learning among students at Pondok Pesantren Darullughah Wadda'wah. A descriptive qualitative approach was employed to illustrate students' experiences in applying these techniques and to analyze their impact on retention and understanding of morphological patterns. The study involved 30 students aged 16–18 years, utilizing instruments such as observation, semi-structured interviews, and documentation. The findings indicate that mnemonics enhance students' memory retention through creative associations such as acronyms, visualizations, and storytelling. Meanwhile, muscle memory strengthens understanding and automates Sharaf patterns through repetitive physical practice, such as writing and verbalizing patterns. This study proposes a learning model called INSTING (Integration of Mnemonics with Training Systems for Memory and Cognitive Development), which combines cognitive and motor aspects to create more adaptive, holistic, and effective learning. These findings contribute not only to innovation in Arabic language teaching but also offer a strategic approach to improving students' retention, comprehension, and motivation in learning Sharaf.